2018
DOI: 10.1038/s41598-018-23036-8
|View full text |Cite
|
Sign up to set email alerts
|

Transcytosis of TrkA leads to diversification of dendritic signaling endosomes

Abstract: The development of the peripheral nervous system relies on long-distance signaling from target organs back to the soma. In sympathetic neurons, this long-distance signaling is mediated by target derived Nerve Growth Factor (NGF) interacting with its axonal receptor, TrkA. This ligand receptor complex internalizes into what is commonly referred to as the signaling endosome which is transported retrogradely to the soma and dendrites to mediate survival signaling and synapse formation, respectively. The molecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 48 publications
0
16
0
Order By: Relevance
“…In the work of Debaisieux and colleagues, other Rabs were also found associated to the purified retrograde carriers, suggesting that subpopulations of Rab7-and Rab5-positive organelles bearing specific small Rab GTPases may constitute alternative pathways with distinct function(s) [24]. Consistent with this hypothesis, it has been reported that the GTPase Rab11, generally associated to recycling cargoes directed to the plasma membrane, is also cotransported in TrkA-containing retrograde carriers in sympathetic neurons [139,140].…”
Section: Roles In Pathologymentioning
confidence: 84%
See 1 more Smart Citation
“…In the work of Debaisieux and colleagues, other Rabs were also found associated to the purified retrograde carriers, suggesting that subpopulations of Rab7-and Rab5-positive organelles bearing specific small Rab GTPases may constitute alternative pathways with distinct function(s) [24]. Consistent with this hypothesis, it has been reported that the GTPase Rab11, generally associated to recycling cargoes directed to the plasma membrane, is also cotransported in TrkA-containing retrograde carriers in sympathetic neurons [139,140].…”
Section: Roles In Pathologymentioning
confidence: 84%
“…These authors showed that, both in cultured neurons and in vivo , TrkA receptors labelled at the distal axon are found in somatic organelles that were positive for a variety of endosomal markers, including Rab7, Rab11, and EEA1. At molecular level, they found that a large proportion of the retrogradely transported TrkA in dendrites was targeted to the cell surface either in the soma or dendrites, prior to being sorted to different populations of endosomes . This novel sorting mechanism may regulate the different outputs of activated receptors, leading to dendrite‐to‐nucleus signalling or local actions (e.g.…”
Section: A New Organelle or A Master Of Disguise?mentioning
confidence: 99%
“…This is in line with a recent study showing that MVB transport NGF-TrkA between the nerve terminals and the cell body in sensory neurons 43 . In sympathetic neurons Rab7 and Rab11 endosomes carry TrkA 44 . We still cannot exclude the possibility that the Rab5 endosomes visualized in axons could be Rab5-to-Rab7 conversion intermediates 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Upon arrival at the cell body, progressive SEs accumulate in perinuclear regions as well as dendrites (Barford et al, 2018; Sharma et al, 2010). Presumably, these locations hint at function.…”
Section: The Signaling Endosome (Se): Specialized Vesicles For Long‐dmentioning
confidence: 99%
“…Do they move retrogradely down the axon as a uniform population and then undergo maturation and molecular diversification in the cell body; or do they travel down the axon prediversified, primed to mediate distinct functions? The answer likely lies somewhere in the middle (Barford et al, 2017, 2018; Scott‐Solomon & Kuruvilla, 2018; Wu et al, 2009; N. Yamashita & Kuruvilla, 2016; M. Ye, Lehigh, & Ginty, 2018).…”
Section: The Signaling Endosome (Se): Specialized Vesicles For Long‐dmentioning
confidence: 99%